ASK1 (MAP3K5) is transcriptionally upregulated by E2F1 in adipose tissue in obesity, molecularly defining a human dys-metabolic obese phenotype - Yulia Haim; Matthias Blüher; Daniel Konrad; Nir Goldstein; Nora Klöting; Ilana Harman-Boehm; Boris Kirshtein; Doron Ginsberg; Tanya Tarnovscki; Yftach Gepner; Iris Shai; Assaf Rudich (Elsevier, 2017)
Objective: Obesity variably disrupts human health, but molecular-based patients' health-risk stratification is limited. Adipose tissue (AT) stresses may link obesity with metabolic dysfunction, but how they signal in humans remains poorly-characterized. We hypothesized that a transcriptional AT stress-signaling cascade involving E2F1 and ASK1 (MAP3K5) molecularly defines high-risk obese subtype. Methods: ASK1 expression in human AT biopsies was determined by real-time PCR analysis, and chromatin immunoprecipitation (ChIP) adopted to AT explants was used to evaluate the binding of E2F1 to the ASK1 promoter. Dual luciferase assay was used to measure ASK1 promoter activity in HEK293 cells. Effects of E2F1 knockout/knockdown in adipocytes was assessed utilizing mouse-embryonal-fibroblasts (MEF)-derived adipocyte-like cells from WT and E2F1−/− mice and by siRNA, respectively. ASK1 depletion in adipocytes was studied in MEF-derived adipocyte-like cells from WT and adipose tissue-specific ASK1 knockout mice (ASK1-ATKO). Results: Human visceral-AT ASK1 mRNA (N = 436) was associated with parameters of obesity-related cardio-metabolic morbidity. Adjustment for E2F1 expression attenuated the association of ASK1 with fasting glucose, insulin resistance, circulating IL-6, and lipids (triglycerides, HDL-cholesterol), even after adjusting for BMI. Chromatin-immunoprecipitation in human-AT explants revealed BMI-associated increased occupancy of the ASK1 promoter by E2F1 (r2 = 0.847, p < 0.01). In adipocytes, siRNA-mediated E2F1-knockdown, and MEF-derived adipocytes of E2F1-knockout mice, demonstrated decreased ASK1 expression and signaling to JNK. Mutation/truncation of an E2F1 binding site in hASK1 promoter decreased E2F1-induced ASK1 promoter activity, whereas E2F1-mediated sensitization of ASK1 promoter to further activation by TNFα was inhibited by JNK-inhibitor. Finally, MEF-derived adipocytes from adipocyte-specific ASK1-knockout mice exhibited lower leptin and higher adiponectin expression and secretion, and resistance to the effects of TNFα. Conclusions: AT E2F1 -ASK1 molecularly defines a metabolically-detrimental obese sub-phenotype. Functionally, it may negatively affect AT endocrine function, linking AT stress to whole-body metabolic dysfunction.